COMPARISON OF RSA AND ROT13 METHODS FOR TEXT FILE CONFIDENTIALITY - Rano, Rano Irawan; Hasugian, Abdul Halim; Sulindawaty (Cattleya Darmaya Fortuna, 2024)
The word cryptography comes from the Greek:krupto (hidden or secret) and grafh (writing),meaning